Gold‐Supported Gadolinium Doped CoB Amorphous Sheet: A New Benchmark Electrocatalyst for Water Oxidation with High Turnover Frequency. (25th February 2020) - ul Haq, Tanveer; Mansour, Said A.; Munir, Akhtar; Haik, Yousef
Abstract: Electrochemical water splitting has been considered a promising approach for green and sustainable hydrogen as a future energy carrier. However, the lack of high performance and inexpensive electrocatalysts for kinetically sluggish oxygen evolution reaction (OER) hinder the practical application. Here, the noteworthy enhancement of electrodeposited cobalt boride (CoB) nanosheets from the combined effect of using gadolinium as a dopant and thin film of gold as prudent support is demonstrated. The free‐standing Gd‐CoB@Au exhibits remarkable electrochemical performance, high intrinsic activity, and lower reaction resistance, which are confirmed by lower onset potential, small charge transfer resistance, lower Tafel slope value, and high turnover frequency. Furthermore, the post‐OER characterization signpost, no observable change in the chemical structure or morphology of nanosheets during the long‐lasting oxidation process. Because of the inexpensive, facile, and scalable one‐step preparation processes, the catalyst is highly encouraging for large‐scale practical applications. Abstract : Oxygen evolution reaction (OER) limits the overall water‐splitting process due to its low rate and sluggish kinetics. Here, a gadolinium doped cobalt boride amorphous sheet is presented that can accelerate the OER process at low onset potential. The novel catalyst exhibits low intrinsic resistance, high turnover frequency (s 1 ), smaller Tafel slope value, and >98% Faradic efficiency.